PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 048472 KUTAMBELIN - Lovriyanti, Triani; Darinda Sofia Tanjung; Eka Kartika Silalahi; Regina Sipayung; Irmina Pinem; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Children Learning In Science (CLIS) learning model on student learning outcomes in the IPAS subject "Magnet: A Mysterious Object" in Grade IV at SD Negeri 048472 Kutambelin for the 2024/2025 academic year. The research employed a quantitative experimental method with a total sample of 30 students. The independent variable was the CLIS learning model, while the dependent variable was student learning outcomes. Data were collected using questionnaires and multiple-choice tests. The average pre-test score was 37.66, increasing to 79.33 in the post-test, while the questionnaire yielded an average score of 75.43. The correlation coefficient was 0.827 (rcalculated ≥ rtable), and the t-test result was 7,796 (tcalculated ≥ ttable), indicating a significant positive effect of the CLIS model on student learning outcomes.